Desenvolvimento de um controlador de luminosidade para LEDs de potência em corrente alternada - Silva, Jailson Fiorini da (2013)
This paper aims to design and build a lighting controller (Dimmer) to power LEDs AC, aiming at a more affordable solution compared to the actual market. Was discussed the theories concerning the modeling of the device, assisting in the preparation and optimization of the device. The control circuit consist of a PIC, which stores the source code to perform the lighting control. The output signal is sent to the PIC drive optocoupler HCPL-314J, which has two independent and isolated channels, and is responsible for driving the MOSFETs present in the circuit AC-AC buck developed. The AC power LED used in this project was the Acriche A3. The entire technical development took place in the laboratories of UTFPR.